Sociology of the arts in action : new perspectives on creation, production, and reception - Rodriguez Morato, Arturo; Santana Acuna, Alvaro (Sociology of the arts,, 2022)
This edited collection carries out an extensive coverage of the sociology of arts' most characteristic thematic areas (production, creation, the artwork, and reception) across an important range of artistic fields, from the most traditional to the more unusual. It makes an argument for the theoretical creativity and empirical expansion that characterizes the study of contemporary sociology of the arts. Such creativity is present in the increasingly predominant approach to a sociology of the arts in action, in all areas of inquiry within the discipline. The range of theoretical paradigms evoked is rich, analysing several of the most important theoretical frameworks currently handled in the discipline (Bourdieu, Becker, Peterson, ANT), and combining them with the works of many other influential contemporary specialists (De Nora, Hennion, Lamont, Menger and Born et al.). The book also establishes links to less known theoretical frameworks and some from different fields including economic sociology,microsociology, ethnomethodology, semiotics, and cultural history. The volume argues that Spanish-speaking scholars are now at the forefront of new developments in the field of the sociology of the arts, and is the first effort to gather research by these influential Spanish-language scholars in a single volume for an English-language audience.